2019
DOI: 10.3889/oamjms.2019.618
|View full text |Cite
|
Sign up to set email alerts
|

Role of Matrix Metalloproteinase-9 in Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: BACKGROUND: Neonatal encephalopathy is a heterogeneous syndrome characterised by signs of central nervous system dysfunction in the newborn. Matrix metalloproteinase-9(MMP-9) increases the blood-brain barrier permeability, and their inhibitors can reduce its damage. MMP-9 has been implicated specifically in cerebral ischemia. AIM: To measure serum MMP-9 in neonatal hypoxic-ischemic encephalopathy and evaluate its correlation to the severity of early prediction and treatment. METHODS: its case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In cases of neonatal HIE, little evidence has shown that the recruitment of peripheral and cerebral immune cells into damaged brain areas play a crucial role in HI brain injury [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], and the level of neutrophil infiltration following HI is associated with an increase in adverse outcomes [ 26 , 27 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of neonatal HIE, little evidence has shown that the recruitment of peripheral and cerebral immune cells into damaged brain areas play a crucial role in HI brain injury [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], and the level of neutrophil infiltration following HI is associated with an increase in adverse outcomes [ 26 , 27 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%